1989
DOI: 10.3177/jnsv.35.303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary pantethine levels on drug-metabolizing system in the liver of rats orally administered varying amounts of autoxidized linoleate.

Abstract: SummaryThe effects of dietary pantethine levels on the drug metabolizing system were investigated under administration of varying amounts of autoxidized linoleate (AL) with rat liver microsomes and S-9 fractions. AL having 800 meq/kg of peroxide value and 1,700 meq/kg of carbonyl value was dosed to the rats of each group given drinking water containing 0mg% (deficient), 6.25mg% (normal), and 125mg% pan tethine (sufficient). The contents and activities of the enzymes in the drug metabolizing system in the rat l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Figure 4 shows that the cytochrome P-450 content in rat liver microsomes increased at first (induction period) and then decreased (reduction period) by the consecutive oral dose of AL for 15 days. Now we can better explain the incompatible phenomena reported previously (5,6) for the changes in cytochrome P-450 content by repeated AL administration. The increase and the decrease of cytochrome P-450 content by repeated AL administration previously reported probably corresponds to observations in the induction and reduction periods, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…Figure 4 shows that the cytochrome P-450 content in rat liver microsomes increased at first (induction period) and then decreased (reduction period) by the consecutive oral dose of AL for 15 days. Now we can better explain the incompatible phenomena reported previously (5,6) for the changes in cytochrome P-450 content by repeated AL administration. The increase and the decrease of cytochrome P-450 content by repeated AL administration previously reported probably corresponds to observations in the induction and reduction periods, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…There have been some incompatible findings on the effect of autoxidized oil on drug-metabolizing activity in rat liver microsomes under the respective experimental conditions (1,2). Therefore, in our previous work (3), AL having 800meq/kg of peroxide value and 1,700meq/kg of carbonyl value was administered periodically for 1-15 days at a daily dose of 2.5ml/kg body weight to male Wistar rats, and the effect of AL on the drug-metabolizing system in rat liver microsomes was studied.…”
mentioning
confidence: 99%
“…In the present study, we determined the changes in contents and compositions of fatty acids and TBA values in liver and the S-9 fraction obtained from rats raised under the same condition as described previously (3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that both the content of cytochrome P-450 and the activity of the drug -metabolizing system were increased by a low dose of AL, and were decreased by a high dose of AL (1) or by the elongation of the dose period even in the case of a low dose of AL (2). We have also investigated the effects of dietary pantethine levels on the drug-metabolizing system in the livers of rat given a low or a high dose of AL (3) . That is, they were induced by the low dose of AL for 5 successive days and lowered by the high dose of AL for the same period, compared with respective non-AL groups in each of the three pantethine levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation